The Relative Contribution of Core Cognitive Beliefs and Metacognitive Beliefs to Depression and Behavioral Activation Factors - Cano-López, Julia B.; García-Sancho, Esperanza; Ramos-Cejudo, Juan; Nordahl, Henrik; Salguero-Noguera, José Martín (Springer Nature, 2025)
Cognitive models have been developed to achieve a comprehensive understanding of depression. Whilst the traditional cognitive model is the most widely tested and emphasizes core cognitions, the metacognitive model emphasizes the role of metacognitions. To determine which belief domain is more relevant in the understanding of depression would have theoretical and clinical implications. However, only a few studies have investigated this issue, and no studies have focused on concomitants of depression beyond symptoms. Thus, our aim was to analyse the relative contribution of core cognitive and metacognitive beliefs to depression and its concomitants. Two cross-sectional studies were carried out. Study 1 (N = 701) examined the relative contribution of core cognitive beliefs and metacognitive beliefs to depressive symptoms in a large sample. Study 2 (N = 293) sought to replicate the results focusing not only on depressive symptoms but also on behavioral activation factors. Regression analyses showed that both core cognitive and metacognitive beliefs significantly contributed to depression and behavioral activation. In both studies, core cogn itive beliefs about disconnection and rejection and negative metacognitive beliefs about social consequences of rumination had unique contributions to depression. Regarding behavioral activation, core cognitive beliefs were consistently associated whereas the contribution from metacognitive beliefs varied: positive metacognitive beliefs added explicative variance to avoidance/rumination, whilst negative metacognitive beliefs about social consequences did so to social impairment. These findings provide additional empirical support for the role of core cognitive beliefs and metacognitions in depression. We discuss clinical implications and future directions.
Keywords: Psicología cognitiva; Depresión mental; Conducta; Ideologías; Core cognitive beliefs; Metacognitive beliefs; Depression; Behavioral activation